YOUTH COUNCILLORS' PERCEPTIONS OF PARTICIPATION AT A MUNICIPAL LEVEL: THE CASE OF A LIMPOPO DISTRICT MUNICIPALITY - Phaswana, Edith Dinong (Africanus: Journal of Development Studies, 2016)
<span style="color: #000000; font-family: 'Arial Narrow', Arial, Helvetica, Tahoma, Geneva, sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Over the past three decades youth participation as a theoretical, practical and policy approach has gained popularity globally. In 1996, South Africa established various youth institutions at national, provincial and local level. This has translated into many adult organisations having to make a shift in their thinking and operations. This includes municipalities at local level. In this paper, I focus on one district municipality in the Limpopo province to examine youth participation practices. I use Driskell and Kudva’s framework of spaces of participation for adult-run organisations seeking to promote youth participation to examine the appropriateness of a municipality as a space for participation practice. My research shows that adult attitudes towards young people can potentially undermine the creation of other participatory spaces However, bounded operational issues can be countered by the structural opportunities existing there.